PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SUBTEMA PELESTARIAN KEKAYAAN SUMBER DAYA ALAM DI INDONESIA - Safira Tyas Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the effect of applying the Discovery Learning model. This study used a quasi-experimental method. The research was conducted at a state elementary school in the city of Bogor, Bogor, in grades IV-A and IV-B in the even semester of 2022/2023. The data processing technique used is the data analysis prerequisite test which includes the normality test and homogeneity test then a hypothesis test is carried out using the t test. based on data analysis, the learning outcomes for the sub-theme of preserving natural resource wealth in Indonesia through the application of the Discovery Learning model obtained an average N-Gain of 70 with a complete learning outcome of 100% while the Picture And Picture model obtained an average N-Gain value of 57 with completeness learning outcomes of 88%. The results of testing the hypothesis stated that H0 was rejected and Ha was accepted because tcount (3.8690) > ttable (2.01174). Based on the results of the research above, it can be concluded that there is an influence of the application of the Discovery Learning model on learning outcomes in the sub-theme of preserving natural resource wealth in Indonesia